ANALISA PENGARUH PELAKSANAAN SISTEM SCAN BARCODE DI TERMINAL KARGO TERHADAP PELAYANAN PENGOPRASIAN KARGO DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ANBUL MADJID LOMBOK - Jefta Geofanny Wahyudi; Abdul Mu’ti Sazali; Linda Winiasri (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The development of the national aviation industry is growing rapidly. This condition makes the flight schedule at Lombok's Zainuddin Abdul Madjid International Airport increasingly crowded. This research was compiled based on observations about the Cargo Terminal unit on the air side of Zainuddin Abdul Madjid International Airport Lombok.The final result achieved from this study is the effect of barcode scanning on time effectiveness and optimizing the performance of cargo personnel in handling cargo goods, in recording SMU numbers (Air Mail). This study aims to determine how much influence the performance of cargo personnel has on recording high school numbers (Surat Muatan Air). Air Charge)